Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/bmjopen-2020-048333
|View full text |Cite
|
Sign up to set email alerts
|

Association between community-based self-reported COVID-19 symptoms and social deprivation explored using symptom tracker apps: a repeated cross-sectional study in Northern Ireland

Abstract: ObjectivesThe aim of the study was to investigate the spatial and temporal relationships between the prevalence of COVID-19 symptoms in the community-level and area-level social deprivation.DesignSpatial mapping, generalised linear models, using time as a factor and spatial-lag models were used to explore the relationship between self-reported COVID-19 symptom prevalence as recorded through two smartphone symptom tracker apps and a range of socioeconomic factors using a repeated cross-sectional study design.Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is because people of disadvantaged communities may not have the same access to outdoor spaces for socialising, there may be differences in the use of restaurants and pubs and differences on the effectiveness of communications aiming to increase compliance with restrictions 5. Understanding the potential differences in effect of control measures by socioeconomic group is important because the pandemic has disproportionally affected more disadvantaged groups 6 7. Interventions designed to control the pandemic may further exacerbate these inequalities if we do not evaluate their differential effects and take actions to mitigate any intervention-generated inequalities 8…”
Section: Introductionmentioning
confidence: 99%
“…This is because people of disadvantaged communities may not have the same access to outdoor spaces for socialising, there may be differences in the use of restaurants and pubs and differences on the effectiveness of communications aiming to increase compliance with restrictions 5. Understanding the potential differences in effect of control measures by socioeconomic group is important because the pandemic has disproportionally affected more disadvantaged groups 6 7. Interventions designed to control the pandemic may further exacerbate these inequalities if we do not evaluate their differential effects and take actions to mitigate any intervention-generated inequalities 8…”
Section: Introductionmentioning
confidence: 99%
“…However, the stay at home index (an indicator of population mobility) was negatively associated with morbidity. Another study showed that the most deprived areas, the region with the lowest employment rate, and higher housing density were associated with higher morbidity 23 …”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the most deprived areas, the region with the lowest employment rate, and higher housing density were associated with higher morbidity. 23 From November 26, 2021 to December 21, 2021, since the emergence of the Omicron variant, the morbidity rate increased slowly. From December 21, 2021 to January 26, 2022, it swiftly reached the peak in just 1 month, demonstrating that the Omicron variant spread rapidly within a short period of time.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
“…those at workplaces, educational facilities, or communal gatherings such as sports or entertainment events), and the load placed upon each STW by industrial activity. Spatial data analysis approaches can be used to characterise the contribution of STW catchments to administrative geographies, which enable greater integration with public health case data (McKinley et al, 2021).…”
Section: Design and Implementation Of Samplingmentioning
confidence: 99%